DEWAN DIREKSI, DEWAN KOMISARIS TERHADAP NILAI PERUSAHAAN KONSUMSI : TOP 20 PERUSAHAAN TERDAFTAR DI BEI - Hurian Kamela (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
The board of directors and commissioners are parties who play a role in the company, especially in corporate decision making. The main objective of this research is to analyze the number of boards of directors and commissioners of firm value. The number of samples based on this study were 20 companies for 4 years (2014-2017). The total sample is 80 observations. The reason the sample was chosen because of the large consumption reasons that had a reputation and were well known in the community. The method used is multiple regression. The dependent variable for the use of measurement that is often used is Tobins-q. The independent variable is based on the measurement of the board of directors and the measurement of the board of commissioners in the company. In addition to this research, the control variables used were Return On Assets (ROA) and total assets. The results of the study explain that there is no effect of the two hypotheses of the board of directors and the board of commissioners on firm value. In general, the number of company leaders has no effect on company activities. The leader of the company has been carrying out its role as a board of monitoring. The contribution of the research is that companies that have carried out good evaluation and selection to increase firm value by implementing the board of directors and commissioners according to the standards.